Description of systemic and intraarticular therapy in a mare with osteoarthritis - Gallego Rodriguez, Renso Sneider (2020)
The case of a 4-year-old criollo female equine which was presented for consultation with a severe increase in the level of the right tarsus and a history of trauma in the tarsal region of the right posterior limb is reported. Severe joint swelling with pain to the touch was evident. Arthrocentesis was performed and haemorrhagic and cloudy joint fluid was obtained, which in the cytological examination showed a moderate leukocyte reaction with a predominance of polymorphonuclear cells. At the radiological evaluation, bone proliferation and periodic reaction, reduction of joint space and lytic areas were observed. In the ultrasound evaluation there was an increase in the size of the joint capsule, a marked increase in the size of the synovial membrane, a severe decrease in joint fluid and the presence of fibrin bands. The therapeutic approach is performed through analgesics, joint lavage and corticosteroid infiltration, and intra-articular infusion with DMSO 10%.